2021
DOI: 10.20469/ijbas.7.10003-2
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Big Five Personality Profiles in Employee Affective Commitment and Engagement: Case of Small and Medium Enterprises

Abstract: With the increase of employee affective commitment and engagement, the likelihood of positive work-related outcomes is enhanced. In turn, companies would benefit in higher productivity and efficacy, reduction in employee turnover, gaining competitive advantage, and overall, becoming more profitable. The Big Five personality profiles are used as predictors of increasing job performance in work environments. Therefore, this study investigates the impact of the Big Five personality profiles on employee affective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Some early scholars found that extraversion relates to work engagement (vigor, dedication, and absorption) [9,10] . In a recent study on 152 employees of small and medium-sized organizations in Bosnia, the researchers found that extroverted individuals showed higher levels of work engagement [30] . A recent study conducted on 383 employees in the information technology sector in India found that extraversion was positively associated with work engagement [31] .…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Some early scholars found that extraversion relates to work engagement (vigor, dedication, and absorption) [9,10] . In a recent study on 152 employees of small and medium-sized organizations in Bosnia, the researchers found that extroverted individuals showed higher levels of work engagement [30] . A recent study conducted on 383 employees in the information technology sector in India found that extraversion was positively associated with work engagement [31] .…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Extant research reported that individuals with high Openness to experience exhibit a high level of work engagement [45][46][47] . In relatively recent studies on the relationship between openness to experience and work engagement, researchers found a strong positive association [4,14,30] . Individuals high on openness tend to exhibit curiosity and creativity linked to finding new ways of engaging in work.…”
Section: The Effect Of Openness To Experience On Vigor Dedication And...mentioning
confidence: 99%
“…The most common types include the Big Five Model, the Myers-Briggs Type Indicator (MBTI), and the Enneagram model (Radisavljević et al, 2022). The Big Five Model categorizes people into five personality types: extroverted, introverted, open-minded, conscientiousness and agreeableness (Hadziahmetovic & Mujezinovic, 2021). The Myers-Briggs Type Indicator categorizes people into four categories: intuitive (N), sensing (S), thinking (T) and feeling (F), with each category containing four similar traits (Amirhosseini & Kazemian, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…The emotional angle affects how employees feel about each of those three variables, regardless of whether they have excellent or negative mentalities toward the association and its leaders. Finally, the physical part of employee commitment concerns the actual energies applied by people to achieve their jobs (Hadziahmetovic & Mujezinovic, 2021;Jiang & Shen, 2020). In their study, Avolio and Gardner (2005) claim that for Authentic Leadership to occur in the workplace, leaders must act upon their true selves and strongly emerge in behaviours such as being honest with oneself than with others.…”
Section: Employee Engagementmentioning
confidence: 99%